Impact of Age, Menopause, and Obesity on Oxylipins Linked to Vascular Health. Issue 2 (February 2021) - Pauls, Samantha D.; Du, Youjia; Clair, Luc; Winter, Tanja; Aukema, Harold M.; Taylor, Carla G.; Zahradka, Peter
Abstract : Objective: Cardiovascular disease, a major cause of mortality and morbidity, exhibits sexual dimorphism since the onset of cardiovascular disease occurs later in women than in men. The loss of cardioprotection in older women may be due to an increase in arterial stiffness after menopause. Free fatty acid metabolites of polyunsaturated fatty acids, called oxylipins, are known to impact vessel function and may be responsible for the vascular benefits of polyunsaturated fatty acids. The objectives of this study were to compare the plasma oxylipin profiles of young females (20–55 years), older females (55 + ), and older males (55 + ) and to identify associations between oxylipins and cardiovascular disease risk factors, such as obesity and arterial stiffness. Approach and Results: We quantified plasma oxylipins by high-performance liquid chromatography–tandem mass spectrometry in archived samples taken from completed clinical trials. We identified 3 major 12-lipoxygenase products, 12-hydroxy-eicosatetraenoic acid, 12-hydroxy-eicosapentaenoic acid, and 14-hydroxy-docosahexaenoic acid, that are present at high levels in young females compared with older females and males. These oxylipins also decreased with obesity and displayed robust negative associations with arterial stiffness as assessed by brachial-ankle pulse wave velocity. According to multiple linear regression modeling, these associations were maintained even after correcting for body mass index category combined with either age, menopausal status, or estradiol levels. Using linear discriminant analysis, the combination of these 3 oxylipins effectively distinguished participants according to both brachial-ankle pulse wave velocity risk group and age. Conclusions: Higher 12-lipoxygenase oxylipin plasma concentrations associated with lower arterial stiffness in premenopausal females may be an important contributing factor to sex differences in cardiovascular disease. Registration: URL: https://www.clinicaltrials.gov ; Unique identifiers: NCT01661543, NCT01562171, NCT01890330, NCT02571114 and NCT02317588. Abstract : Supplemental Digital Content is available in the text.